Tri-reforming of CO2-rich natural gas: equilibrium analysis and reactor technology evaluation. - Jardim, Samuel Sanchez Queiroz (2019)
The tri-reforming of methane was studied for converting natural gas, rich in CO2, into syngas suitable for the industry. The reaction was evaluated at typical industrial pressure by performance indicators, such as carbon dioxide conversion, syngas yield, syngas ratio, and coke production. Three possible reactor configurations were investigated and compared, seeking industrial applicability and good performance, encompassing the membrane, autothermal and heated reactors. The study employed two approaches: (i) analysis of reaction equilibrium and (ii) simulation of first-principle reactor models. The tri-reforming equilibrium was analyzed varying the chemical composition and temperature at 25 bar, either in adiabatic or isothermal conditions. In turn, the reactor simulations evaluated the behavior of each specific configuration and compared their performance, addressing issues such as coke deposition and temperature profile. The equilibrium data showed the need for high concentration of oxygen in the feed to drive the adiabatic reaction, around 50% of O2/CH4 in molar proportion, thus, demanding a special reactor to manage the temperature. The adiabatic data also revealed a trade-off between carbon-dioxide conversion and syngas ratio. However, when the reaction temperature was maintained by an external heat source, the trade-off disappears and performance is enhanced. Concerning the reactor simulations, the results indicated that membrane reactors (for oxygen distribution) for tri-reforming are unsuitable for the industry due to problems with coke deposition. In addition, the reactor comparison showed an outperformance of the heated over the autothermal reactor. It had superior syngas yield and carbon dioxide conversion in the two cases tested. However, when the furnace emission of CO2 was accounted, the overall conversion of the heated reactor was inferior to the autothermal one. Up to 52% of carbon dioxide conversion was attained by tri-reforming as well as 83% of syngas yield. In summary, the results from the equilibrium data and reactor simulations endorsed the expectations concerning the applicability of tri-reforming to convert syngas from resources concentrated in CO2, with the caveat concerning temperature and solid carbon deposition.